Sistem Informasi Manajemen Aset Berbasis Web Dengan Fitur Scan Barcode Untuk Identifikasi Aset - Yahya, Hafid; Fahmi, Dicky; Alvin Faga, Daniel; Haryono, Wasis (CV. Multi Kreasi Media, 2025)
Optimal asset management is essential in supporting smooth business operations, including at PT. Datanex Inovasi Pratama. This study aims to design and implement a web-based asset management information system equipped with barcode scanning functionality for digital asset identification. The development follows the Waterfall methodology, consisting of sequential stages: analysis, design, development, testing, and deployment. The resulting system is capable of recording asset details, managing borrowing and return processes, and monitoring asset transfers and maintenance efficiently. Laravel was selected as the development framework due to its modular and structured nature. This system is expected to enhance data accuracy, streamline operations, and reduce errors in asset management workflows.